ALK phosphorylates SMAD4 on tyrosine to disable TGF-β tumour suppressor functions - Zhang, Qianting; Xiao, Mu; Gu, Shuchen; Xu, Yongxian; Liu, Ting; Li, Hao; Yu, Yi; Qin, Lan; Zhu, Yezhang; Chen, Fenfang; Wang, Yulong; Ding, Chen; et al. (Nature cell biology, 2019)
Loss of TGF-β tumour suppressive response is a hallmark of human cancers. As a central player in TGF-β signal transduction, SMAD4 (also known as DPC4) is frequently mutated or deleted in gastrointestinal and pancreatic cancer. However, such genetic alterations are rare in most cancer types and the underlying mechanism for TGF-β resistance is not understood. Here we describe a mechanism of TGF-β resistance in ALK-positive tumours, including lymphoma, lung cancer and neuroblastoma. We demonstrate that, in ALK-positive tumours, ALK directly phosphorylates SMAD4 at Tyr 95. Phosphorylated SMAD4 is unable to bind to DNA and fails to elicit TGF-β gene responses and tumour suppressing responses. Chemical or genetic interference of the oncogenic ALK restores TGF-β responses in ALK-positive tumour cells. These findings reveal that SMAD4 is tyrosine-phosphorylated by an oncogenic tyrosine kinase during tumorigenesis. This suggests a mechanism by which SMAD4 is inactivated in cancers and provides guidance for targeted therapies in ALK-positive cancers. Zhang et al. show that ALK phosphorylates SMAD4 at Tyr 95 to block its binding to DNA, representing a mutation-independent mechanism for blocking the tumour suppressor function of TGF-β in ALK-positive cancers.